Managing patients' no-show behaviour to improve the sustainability of hospital appointment systems: Exploring the conscious and unconscious determinants of no-show behaviour. (1st October 2020) - Hu, Miao; Xu, Xiaoyan; Li, Xiaodong; Che, Tong
Abstract: A hospital appointment system promotes information exchange between hospitals and patients. Because patients' no-show behaviour wastes medical resources and compromises the sustainability of medical services, it is of utmost importance to expound no-show behaviour and its determinants. From a multi-stage perspective, we identify channel convenience, waiting time, and expected technical quality as conscious determinants and no-show habit as an unconscious determinant and propose a model for analysing patients' no-show behaviour. The proposed hypotheses are examined with data collected from a Chinese tertiary care public hospital's appointment system by binary logistic regression. The results show that channel convenience and expected technical quality are negatively related to no-show behaviour whereas the effects of waiting time and no-show habit on no-show behaviour are significantly positive. Meanwhile, the relationship between no-show habit and no-show behaviour is stronger for shorter waiting time or higher levels of channel convenience and expected technical quality. Our findings have implications for managing patients' no-show behaviour, improving hospital appointment system management, and providing sustainable medical services. Highlights: Managing no-shows can improve the sustainability of hospital appointment systems. Examine the determinants of no-show behaviour from a multi-stage perspective. Emphasize the influences of unconscious determinants on no-show behaviour. The moderating effects of conscious determinants have been analysed.